ANALISIS PENGARUH CUSTOMER ENGAGEMENT TERHADAP REPURCHASE INTENTION DENGAN BRAND EQUITY DAN SOCIAL MEDIA AGILITY SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGGUNA SMARTPHONE IPHONE APPLE) - Sakti Edi Saputra; Imroatul Khasanah (Diponegoro Journal of Management, 2022)
The use of smartphones can’t be separated from life today. One of the premium brands in smartphones is the iPhone which is carried by Apple Inc. However, the iPhone market in Indonesia has decreased in terms of sales and also the top brand index. The data used were obtained from 120 respondents who use iPhone in the city of Semarang. The data obtained were analyzed quantitatively and structurally using the Structural Equation Modeling (SEM) method using the Analysis Moment of Structural (AMOS) 24 program. The findings from this study show that customer engagement has a positive and significant effect on brand equity and perceived social media agility, and also brand equity and perceived social media agility have a positive and significant effect on repurchase intentions.